HIERARCHICAL STRUCTURE OF THE UNIVERSE - Zakhozhay, V. A. (Одеські астрономічні публікації, 2018)
The modern understanding of the structure of the Universe is discussed. The Solar System is viewed as an ordinary planetary system. The neighbourhood of the Sun is specified starting with the nearest stars and nearby clusters and working outward through the Local system of stars, in particular, Gould’s belt. The subgroups of the Milky Way, our stellar system, and Andromeda are examined as components of the Local Group of galaxies. Special attention is paid to their astrophysical, kinematic and dynamic properties. A larger agglomeration of galaxies, called the Local Supercluster, which contains the Local Group and its immediate neighbourhood is analysed. And finally, the Laniakea hypercluster to which the Local Supercluster and its environment belong is described along with its neighbours, namely the Perseus-Pisces hypercluster and the Local Void.